A NARRATIVE INQUIRY OF TEACHING TRANSLATION FOR ENGLISH DEPARTMENT STUDENTS - Jumainah Jumainah (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2021)
The focus of this study is to share how to teach translation to the English Department students. Majoring in English does not instantly qualify the students as good translators. As a lecturer frequently assigned to teach translation classes, thereseacher finds that teaching translation to the English Department students is often as challenging as the translation process itself. Therefore, this paper is presented as the researcher’s shares of contribution to the field of translation teaching and training. The approach applied in this study is narrative inquiry.The researcher narrates the stories of how to teach translation based on her personal teaching experiences since 2015. The findings on how to teach translation are arranged into three orders: pre-teaching preparation, while teaching focus, and after teaching focus. The results of this study are expected to give insights and ideas for fellow translation lecturers and learners.